Studying the Effect of Abundance of Natural Resources on Economic Growth - Amini, Abbas (European Journal of Sustainable Development, 2018)
The tendency towards a better life and improvement of life status has always had a priority among human communities. The approach utilized by economics and specifically the growth and economic development activities refers to the improvement of the material dimension. Meanwhile, some countries are rich and some suffer from poverty. Therefore, to recognize basic growth factors and the roots of income inequality among different nations, the role of factors such as institutions, culture, and geography has been emphasized. Natural resources, from among geographical elements, are considered highly important. On the other hand, many communities that exploit a vast amount of natural resources have encountered failure in reflecting appropriate economic performances and this has often had unpleasant outcomes and resource curse has been commonly used to describe this phenomenon. Thus, the goal of the present research is to find out about the nature of resource curse phenomenon and studying different structures that affect natural resources' abundance on economic growth and development. Accordingly, some of the most important effectiveness structures of natural resources have been investigated as: long-term approaches in global prices, price fluctuations, permanent reductions in industry parts, colonialism institutions and eligibility, lack of institutions that strengthen inconsistency and chaos, cyclical nature of Netherlander disease. This study has investigated about 22 advanced countries and 61 underdeveloped and developing countries within the time period between 1996 and 2010. For both countries, we have first used group effects' meaningfulness test to recognize the nature of data (pooled or panel) and Brush-Pagan and Haussmann tests to recognize the difference between fixed and random effects, and then the research model was estimated using fixed effects method. The research findings showed that natural resources abundance, institutions, and interactions between institutions, and natural resources did not have a meaningful effect on average yearly growth rate of GDP. The final conclusion of the different strategies of effectiveness of natural resources does not mean that the need to mineral materials as the wealth necessarily would lead to the lack of the economic and political developments through many of such strategies. In return, it would be better to view the resource abundance as a two sided coin which is endowed with both advantages and risks. As much as it can be exploited for unnecessary expenses, its proper use can lead to lots of benefits. Keywords: abundance of natural resources, resource curse, economic growth, institutions, policies